Analytical-Comparative Study of Iraqi and American Light Oil Components by Gas Chromatography-Mass Spectrometry - Hassan, F A; Hussain, K I; Alassaf, N A (Al-Nahrain Journal of Science, 2018)
The analysis of Iraqi light oil (light naphtha (by capillary gas chromatography- mass spectrometry (GC-MS) was performed by the injection of whole naphtha sample without use of solvents. Qualitative analysis and the identification of the hydrocarbon constituents of light naphtha was performed and comparison had been done with American light oil (light naphtha). The obtained results showed a major difference between the tow light naphtha.